The Effect of Compensation, Commitment and Work Discipline on Employee Performance: Pengaruh Kompensasi, Komitmen dan Disiplin Kerja Terhadap Kinerja Karyawan - Oktaviani, Ika; Kusuma, Kumara Adji (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of compensation, commitment and work discipline on employee performance at CV. Indo Prima Plastik. This research uses quantitative research with hypothesis testing. The sample used in this study were 50 employees at CV. Indo Prima Plastik. The analytical tool used in this research is using IBM SPSS statistical software version 2.5.0, this study aims to determine the effect of compensation, commitment and work discipline. Primary data in this study were obtained from questionnaires. The results of this study prove that (1) compensation has an effect on employee performance, (2) commitment has an effect on employee performance, (3) work discipline has an effect on employee performance.